Filipinos Represent : DJs, Racial Authenticity, and the Hip-hop Nation - Tiongson, Antonio T., Jr., 1968- (Book collections on Project MUSE., 2013)
Antonio T. Tiongson draws on interviews with Bay Area-based Filipino American DJs to explore the authenticating strategies they rely on to create a niche within DJ culture. He shows that while the engagement of Filipino youth with DJ culture speaks to the broadening racial scope of hip-hop, such involvement also upholds deracialized accounts of hip-hop and renders difference benign.